2013
DOI: 10.1021/jm301859s
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 4-{4-[(3R)-3-Methylmorpholin-4-yl]-6-[1-(methylsulfonyl)cyclopropyl]pyrimidin-2-yl}-1H-indole (AZ20): A Potent and Selective Inhibitor of ATR Protein Kinase with Monotherapy in Vivo Antitumor Activity

Abstract: ATR is an attractive new anticancer drug target whose inhibitors have potential as chemo- or radiation sensitizers or as monotherapy in tumors addicted to particular DNA-repair pathways. We describe the discovery and synthesis of a series of sulfonylmorpholinopyrimidines that show potent and selective ATR inhibition. Optimization from a high quality screening hit within tight SAR space led to compound 6 (AZ20) which inhibits ATR immunoprecipitated from HeLa nuclear extracts with an IC50 of 5 nM and ATR mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
171
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(175 citation statements)
references
References 40 publications
4
171
0
Order By: Relevance
“…We also demonstrated that pDNA-PKcs provided a functional, sensitive PD readout for ATR inhibition that was proportional to drug exposure up to 10 mg/kg and associated with maximal antitumor activity. To date, two small-molecule ATR inhibitors have been reported in the literature (13)(14)(15); however, little is known about the requirements of ATR target engagement and PD-efficacy relationships. Using the GRANTA-519 model, the following parameters were considered: the extent and duration of the pDNA-PKcs PD response, and ATRi PK.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also demonstrated that pDNA-PKcs provided a functional, sensitive PD readout for ATR inhibition that was proportional to drug exposure up to 10 mg/kg and associated with maximal antitumor activity. To date, two small-molecule ATR inhibitors have been reported in the literature (13)(14)(15); however, little is known about the requirements of ATR target engagement and PD-efficacy relationships. Using the GRANTA-519 model, the following parameters were considered: the extent and duration of the pDNA-PKcs PD response, and ATRi PK.…”
Section: Discussionmentioning
confidence: 99%
“…Replication stress, in the absence of ATR can result in unrepaired stalled forks that will collapse into DSBs and eventually lead to cell death. There are several synthetic lethalityinducing agents currently targeting the ATR-CHK1 pathway with promising preclinical and/or clinical trial results (13)(14)(15)(16). To date, two small-molecule ATR inhibitors have been reported in the literature (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective ATR inhibitors only started to emerge in 2011 and were derived by independent strategies [81,[86][87][88]. In our case, we employed a screening based on a cellular model of "at will" ATR activation upon the addition of an inert derivative of tamoxifen [81].…”
Section: Targeting Rs In Cancer Treatmentmentioning
confidence: 99%
“…Promising results with ATR inhibitors in vivo are also starting to emerge. For instance, these compounds limit the growth of colon cancer xenograft models with high basal levels of RS [86]. It should be noted that a recent work has identified that ATR is also essential for the activation of a checkpoint that responds to mechanical and osmotic stress, and which coordinates chromatin condensation with the breakdown of the nuclear envelope [94].…”
Section: Targeting Rs In Cancer Treatmentmentioning
confidence: 99%